Problematyka wymogów etycznych dotyczących osoby notariusza i sporządzanych przez niego czynności - Stawecki, Marek (Annales. Etyka w Życiu Gospodarczym, 2008)
The fundamental rules which should be followed by Notary Public are: honesty, reliability,detachment and impartiality, as well as keeping the professional secret.As a crucial participant in creating and carrying into effect legal structures of free market, NotaryPublic performs public functions. Therefore, he or she is authorized to give an official character todeclarations of persons being their clients. In view of the foregoing, the notary should secure suchdocuments in trading abiding by the rules and regulations of the governing law and ethics.With a view to a special role of the profession in question in economic trade, The National NotaryBoard passed a Notary Public Code of Professional Ethics, by virtue whereof a Notary shall with theirattitude and actions give a good character to their profession and mind its dignity and honor. Anybreach of the above – mentioned rules results in the Notary’s liability.Notary Public, as a person whose functions play a crucial role in legal trade and who is trusted bythe parties, is responsible for correctness and precision of their activities. Their liability as clients’confidant may result in civil, legal, disciplinary and tax liability.